(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda being the science of life, primarily focuses on enhancing health of healthy individuals and removal of disease causing entities in a diseased person. Swarna (gold) has substantial therapeutic value, which has been indicated in different classics of Ayurveda. Swarna (gold) is desired by every human for many centuries. The desire is not only for its ornamental or commercial value but also because of its great medicinal value by which it increases strength and immunity. Swarna is converted into suitable dosage forms like Parpati, Pottali, Vati etc. Swarna kalpas are the unique blend of herbomineral formulations where Gold is used as one of the main ingredient. Swarna kalpas are widely used as therapeutic as well as life saving agents (in some emergencies). These formulations are helpful in treating many chronic disease conditions but it also acts miraculous when used for Rasayana purpose. In this review most commonly used Swarna kalpas such as Yogendra ras, Rasraj Ras, Vasant Kusumakar ras, Swarna malini vasant are discussed on the basis of different therapeutic angles